CONFLICT OF INTEREST PREVENTION STRATEGY IN ERADICATING CORRUPTION IN INDONESIA (Lex Jurnalica, 2020)
A conflict of interest occurs when personal interests mix with official duties and responsibilities. This can be seen from the conflicts of interest that often occur and are faced by State Administrators, among others, the process of making State Administrators policies that take sides with a party due to influence / close relationship / dependence / gratification; or the tendency to use important State assets and information for personal gain; for example social assistance. In other words, a conflict of interest arises when someone can abuse their position for personal or corporate gain. The aim in this organization is to prevent the occurrence of enforcing conflicts and corruption. Related to this, it is a strategy to prevent conflicts of interest in eradicating corruption in Indonesia. To support this, it is used in data studies in the form of descriptive analysis studies through various literature studies.Â Keywords: Conflict of Interest, Corruption, State Officials